Structural characterization and anti-proliferative activities of partially degraded polysaccharides from peach gum. (1st January 2019) - Wei, Chaoyang; Zhang, Yu; He, Liang; Cheng, Junwen; Li, Junhui; Tao, Wenyang; Mao, Guizhu; Zhang, Hua; Linhardt, Robert J.; Ye, Xingqian; Chen, Shiguo
Graphical abstract: Highlights: LP fractions were prepared from peach gum of Prunus persica Batsch. They were AG II arabinogalactans with β-d -(1→6)-galactan backbone. Their molecular weight and chain conformation were investigated. Their binding affinities to galectin-3 and anti-tumor activities were investigated. LP fractions could express their anti-tumor activity by binding to Gal-3. Abstract: LP100R, LP10R and LP5R were isolated from peach gum by ultrafiltration. They were identified as AG II arabinogalactans composed of mannose, rhamnose, glucuronic acid, galactose, xylose and arabinose, which had a β-d -(1→6)-galactan backbone and were branched at O-3 and O-4. LP100R, LP10R and LP5R exist in a spherical conformation with the molecular weight of 8.50 × 10 4 g/mol, 4.77 × 10 4 g/mol and 2.40 × 10 4 g/mol, respectively. The binding affinities of LP fractions to galectin-3 (Gal-3) were 0.77 μM for LP100R, 2.88 μM for LP10R and 5.15 μM for LP5R, respectively. Meanwhile, an anti-proliferative assay revealed that LP100R possessed higher anti-proliferative activity against HepG2 cells (IC50, 4.5 mg/mL) and MCF-7 cells (IC50, 0.43 mg/mL) than did LP10R and LP5R, which were in accordance with their binding affinities to galectin-3. Therefore, LP fractions (especially LP100R) might exert the anti-tumor activity by directly inhibiting the Gal-3 mediated proliferation of cancer cells.